Societal dimensions of environmental science : global case studies of collaboration and transformation - Lopez, Ricardo D. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"This book brings together several key examples of the successes and the challenges that exist for environmental stakeholders trying to strike a balance between science and the societal implications of the issues involved. It provides important methods and approaches necessary for informed decision making and a better understanding of the common threads of learning, collaboration, negotiation, and compromise. It also explains the concepts and skills needed to better understand how specific project goals can be best achieved in the rapidly-changing field of environmental management, by providing practical situations and solutions, across a global landscape"--
OCLC-licensed vendor bibliographic record.
Keywords: Environmental sciences -- Social aspects; Environmental sciences -- Public opinion; Environmental policy -- International cooperation; Environmental protection -- International cooperation; Globalization -- Environmental aspects; SCIENCE / Environmental Science; LAW / Environmental; NATURE / Environmental Conservation & Protection; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development